2013
DOI: 10.3402/ljm.v8i0.21674
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytosis as a prognostic marker in the development of fetal inflammatory response syndrome

Abstract: ObjectiveTo identify and evaluate the correlation between leukocyte count in maternal blood and the risk of developing fetal inflammatory response syndrome (FIRS).Patients and methodsThe study involved 158 infants born at 22−34 weeks of gestation and their mothers. Umbilical cord blood cytokines were evaluated in immunoassay tests and maternal blood was tested for the leukocyte formula.ResultsThe period of gestation was significantly shorter in the FIRS group compared to the control group (29.5±3.1 vs. 32.2±2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The continuum of infection, FIRS, funisitis, and chorioamnionitis requires the activation of umbilical cord endothelial cells and the infiltration of maternal inflammatory cells across the placental layers toward the fetus. For example, FIRS is associated with maternal peripheral blood leukocytosis ( Bartkeviciene et al, 2013 ), and a predominance of activated neutrophils and monocytes in the cord blood of newborns with funisitis ( Kim et al, 2009 ). In contrast, in LPS-stimulated term umbilical cord blood neutrophils, bilirubin, a product of the HO reaction, induces antioxidants superoxide dismutase (SOD) and HO-1 expression and decreases the production of the inflammatory cytokine IL-8 and the chemokine MIP-1β in a dose-dependent manner, conferring protection from LPS ( Weinberger et al, 2013 ).…”
Section: Types Of Pathological Pregnancies and The Protective Role Ofmentioning
confidence: 99%
“…The continuum of infection, FIRS, funisitis, and chorioamnionitis requires the activation of umbilical cord endothelial cells and the infiltration of maternal inflammatory cells across the placental layers toward the fetus. For example, FIRS is associated with maternal peripheral blood leukocytosis ( Bartkeviciene et al, 2013 ), and a predominance of activated neutrophils and monocytes in the cord blood of newborns with funisitis ( Kim et al, 2009 ). In contrast, in LPS-stimulated term umbilical cord blood neutrophils, bilirubin, a product of the HO reaction, induces antioxidants superoxide dismutase (SOD) and HO-1 expression and decreases the production of the inflammatory cytokine IL-8 and the chemokine MIP-1β in a dose-dependent manner, conferring protection from LPS ( Weinberger et al, 2013 ).…”
Section: Types Of Pathological Pregnancies and The Protective Role Ofmentioning
confidence: 99%
“…Therefore, as stated by Bartkeviciene, leukocyte count guides practitioners to predict FIRS. 23 Hoffer compared the correlation between FIRS and adverse neonatal outcome between neonates less than 32 weeks' GA with neonates 32 weeks or longer, it shows nearly significant result (P= 0.065). 27 In our prediction model, the combination of leukocyte counts and GA at PPROM increased the AUC, from 0.68 and 0.81 respectively as sole predictors, to 0.82 for final model to predict BA (Figure 1-3).…”
Section: Discussionmentioning
confidence: 98%
“…Before labor, maternal leukocytes count of 11,810/mm3 could predict FIRS with the AUC of 0.61 (95% CI 0.50-0.71). 23 FIRS defined by fetal plasma interleukin-6 (IL-6) concentrations >11 pg/mL. 24 It significantly correlated with spontaneous preterm delivery among PPROM women.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that deletion of Lhcgr caused an over twofold enlargement of the HSC pool in the bone marrow (Fig I, J and N), which was accompanied with significantly increased bone marrow cellularity (Fig H) and leukocytosis in the peripheral blood (Fig A–H). Clinically, leukocytosis is a potential risk factor of thrombosis (Carobbio et al , ; De Stefano et al , ) and many inflammatory diseases (Erlinger et al , ; Karthikeyan & Lip, ; Bartkeviciene et al , ; Jo et al , ). The abnormally elevated hematopoiesis in mice was also associated with faster leukemia development in an MLL‐AF9‐induced AML model (Fig ).…”
Section: Discussionmentioning
confidence: 99%